Low voltage ride through capability enhancement of grid connected large scale photovoltaic system - Saeedul Islam, G.; Al-Durra, A.; Muyeen, S.M.; Tamura, J. (2011)
Recently interest in photovoltaic (PV) power generation systems is increasing rapidly and the installation of large PV systems or large groups of PV systems that are interconnected with the utility grid is accelerating. To maintain the grid stability due to the huge penetration of photovoltaic power to the grid, much stricter grid codes are being imposed by the energy regulatory bodies. This paper discusses the detailed modeling and control strategies of a large scale grid connected photovoltaic system that can help to augment the low voltage ride thorough capability of DC based PV plant. It should be noted that grid side inverter plays an important role in low voltage ride through and therefore, overvoltage and undervoltage tripping of DC link of the grid tied inverter should be avoided, if possible. This study attempts to incorporate DC link over and under voltage protection in the control loop without increasing overall cost of protective device, which is another salient feature of this study. Furthermore, a comparative study with conventional inverter scheme is carried out. Different types of fault scenarios are analyzed to demonstrate the effectiveness of the overall control scheme, where recent grid code for distribution generation system is considered.